Effect of Online and Offline Self-Management Programs on Blood Pressure Control Among Ordinary Parliamentary Officials of the Secretariat of the House of Representatives with Uncontrolled Hypertension - Chaiphattharatada, Itsaya; Khungtumneam, Kamontip; Kompayak, Jariyawat (Journal of Health Sciences and Wellness, 2025)
Uncontrolled hypertension increases the risk of coronary heart disease, stroke, chronic kidney disease, and premature death. A large number of Thai ordinary parliamentary officials suffer from uncontrolled hypertension, often due to a lack of self-awareness and inconsistent health behaviors for hypertension control. Therefore, self-management is needed to help control hypertension. This quasi-experimental study aimed to compare blood pressure levels between civil servants who received online and offline self-management programs. The sample consisted of 50 Thai ordinary parliamentary officials, divided into two groups: 25 who received the online program and 25 who received the offline program. The sample was selected based on inclusion criteria and random assignment to the groups. The research instruments included online and offline self-management programs and a blood pressure monitor. Data analysis was conducted using descriptive statistics and t-tests. The results of the study indicated that, after completing the 12-week trial, the group receiving the online program showed a statistically significant difference in the mean systolic and diastolic blood pressure levels compared to the group receiving the offline program, at the 0.05 significance level. Based on the results of this study, nurses can use the online program to promote healthy behaviors that help control hypertension and prevent complications.